KONSEP DASAR SEMIGRUP REGULER REDUKTIF - Elvinus R. Persulessy (Barekeng)
In this paper, we consider the properties of reductive semigroups, with two congruence relations defined on them, which gave a characterization for regular reductive semigroups.